2007
DOI: 10.1016/j.lisr.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Fiction access points across computer-mediated book information sources: A comparison of online bookstores, reader advisory databases, and public library catalogs

Abstract: One of a librarian's more difficult jobs may be helping patrons in an elusive search for a "good book." A variety of online sources are now available to help readers and librarians in their search, but the descriptive capabilities of the resources vary widely. Library and information science (LIS) literature has suggested many schemes and access points for fiction classification.This study compared the records for identical books in a variety of computer-mediated book information sources (CMBIS) in order to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 3 publications
1
26
0
Order By: Relevance
“…If readers wish to find good reads from authors they do not know, traditional search systems do not help much [1]. If users invent keywords like in topical search, the system ranks the results by topical relevance.…”
Section: Selecting Fiction and Non-fictionmentioning
confidence: 99%
See 1 more Smart Citation
“…If readers wish to find good reads from authors they do not know, traditional search systems do not help much [1]. If users invent keywords like in topical search, the system ranks the results by topical relevance.…”
Section: Selecting Fiction and Non-fictionmentioning
confidence: 99%
“…E.g. Adkins and Bossaler [1] argue that online catalogs are effective in known author or known title searches, but not as effective in supporting browsing books for other purposes. They call for studies on actual fiction searching practices of readers using electronic access tools like catalogs to determine how those readers make book selection decisions in the absence of the physical book.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the library catalog records, where greater subject access is provided for nonfiction titles in the form of subject headings and classification numbers, may provide fewer access points than those records that contain user-generated content. 5 Library catalog records are not particularly good at describing the effect of a fiction title, that is, its tone, its emotional impact on the reader, and the memories or associations that it can invoke in readers. The importance of providing access to effect has been emphasized by Wyatt, who suggests that fiction works should be classified by feeling rather than subject.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors concluded that the library catalog records, where greater subject access is provided for non-fiction titles in the form of subject headings and classification numbers, may provide fewer access points than those records that contain user-generated content. 29 A variety of tools have been developed or adapted for use in RA services, such as NoveList (http://www.ebscohost.com/novelist/) and What Should I Read Next (http://www.whatshouldireadnext.com/); these databases provide valuable resources to advise RA librarians with ways to connect users to their reading interests. RA librarians can also make use of social reading sites such as LibraryThing, Goodreads, and Shelfari (http://www.shelfari.com/), which allow users to document, discuss, and share their reading interests.…”
Section: Literature Reviewmentioning
confidence: 99%